Coping strategies and resilience among patients with hypertension in Ghana - Boima, Vincent; Yorke, Ernest; Ganu, Vincent; Gyaban-Mensah, Anna; Ekem-Ferguson, George; Kretchy, Irene Akwo; Mate-Kole, Charles Christopher (Frontiers in Psychology, 2023)
Background Hypertension is associated with high morbidity and mortality and this has been linked to poor treatment and control rates. To optimise drug treatment, patient centered strategies such as coping, resilience and adherence to medication may improve control rates and decrease the morbidity and mortality associated with hypertension. This study therefore assessed coping skills and resilience among patients with hypertension in Ghana. Methods A cross-sectional study was conducted in Korle Bu Teaching Hospital. 224 patients with a diagnosis of hypertension were consecutively selected from an outpatients clinic in a national referral centre in Ghana. They consented to participate in the study. They were administered questionnaires comprising socio-demographic characteristics, clinical parameters, Adult Resilience Measure, and the Africutural Coping Systems Inventory were collected. Data were analysed using Stata version 16.1 and significance level was set at p value of ≤ 0.05. Results The mean age of participants was 62.03±11.40 years and the majority were male (63%). The overall coping strategy mean score was 43.13±13.57. For Resilience, median caregiver and personal resilience scores were 32(IQR-7) and 39(IQR-9) respectively. Increased systolic BP significantly increases the overall coping strategy score. Collective coping strategy (having 3 or more friends) and systolic BP significantly increased coping strategy (95%CI=0.05 to 3.69 vs 95%CI=0.58-5.31). Overall coping strategy significantly increased personal resilience and relational resilience domains scores by 0.004(95%CI=0.002 to 0.01) and 0.005(95%CI=0.003 to 0.006) units respectively among the patients. This study demonstrated that Cognitive and emotional debriefing coping strategy was mostly used by patients with hypertension. Conclusion This study demonstrated association between coping strategy and diastolic and systolic blood pressure with age and social support increasing cognitive coping strategy. Coping strategies had a positive and significant correlation with Personal and Caregiver Resilience, specifically collective and cognitive debriefing significantly improved resilience among study participants. Measures that can improve the coping strategies and resilience among patients with hypertension will enhance patients’ understanding regarding behavioural changes that will lead to a better outcome of their management.